2009
DOI: 10.1007/s11433-009-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

The optimal path of piston motion for Otto cycle with linear phenomenological heat transfer law

Abstract: An Otto cycle engine with internal and external irreversibilities of friction and heat leakage, in which the heat transfer between the working fluid and the environment obeys linear phenomenological heat transfer law [q ∝ Δ(T −1 )], is studied in this paper. The optimal piston motion trajectory for maximizing the work output per cycle is derived for the fixed total cycle time and fuel consumed per cycle. Optimal control theory is applied to determine the optimal piston trajectories for the cases of with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Considering the influences of convective-radiative HTA (q « ∆(T) + ∆(T 4 )), Burzler and Hoffman [274,275] derived the OPM in compression and power strokes of a four stroke Diesel engine with MP as the OPB when the WF was non-ideal. Fixing total cycle time and fuel consumed per cycle, Xia et al [276] investigated the OPM trajectory of an Otto cycle engine for MW when HTA between WF and the environment obeys a linear phenomenological HTA (q « ∆(T´1)), and found that work output and efficiency could improve by more than 9% after optimizing the piston motion. Xia et al [277] and Chen et al [278] applied the finite combustion rate model in [259], derived the OPM trajectories of irreversible Diesel cycle engine for MW when HTA between WF and the environment obeys a linear phenomenological HTA [277] and generalized radiative HTA [278], respectively, and examined the influence of HTA on the OPM trajectories.…”
Section: The Influence Of Hta On the Optimum Cycle Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the influences of convective-radiative HTA (q « ∆(T) + ∆(T 4 )), Burzler and Hoffman [274,275] derived the OPM in compression and power strokes of a four stroke Diesel engine with MP as the OPB when the WF was non-ideal. Fixing total cycle time and fuel consumed per cycle, Xia et al [276] investigated the OPM trajectory of an Otto cycle engine for MW when HTA between WF and the environment obeys a linear phenomenological HTA (q « ∆(T´1)), and found that work output and efficiency could improve by more than 9% after optimizing the piston motion. Xia et al [277] and Chen et al [278] applied the finite combustion rate model in [259], derived the OPM trajectories of irreversible Diesel cycle engine for MW when HTA between WF and the environment obeys a linear phenomenological HTA [277] and generalized radiative HTA [278], respectively, and examined the influence of HTA on the OPM trajectories.…”
Section: The Influence Of Hta On the Optimum Cycle Pathmentioning
confidence: 99%
“…Using the heat engine models established in [257,258,272,276], Ge [84] obtained the OPM trajectories of an Otto cycle for MEG which was generated by FL, HTL and pressure drop loss, as well as for MEF, respectively, when the HTA obeys generalized radiative HTA, and the results obtained included the OPM trajectories for MEG [272,289] and MEF with linear phenomenological HTA [272] and radiative HTA [289]. The OPM trajectories on power strokes of an irreversible Otto cycle for MEG and MEF when HTA obeys generalized radiative HTA are determined by following differential equations [84]:…”
Section: The Influence Of Hta On the Optimum Cycle Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on irreversible thermodynamics, some scholars used finite-time thermodynamics (FTT) or entropy generation minimization (EGM) [18][19][20][21][22][23][24][25][26][27][28][29][30] to optimize the heat transfer process, which was also called thermodynamic optimization. The entropy generation minimization is a heat transfer optimization aiming at exergy lost minimization, but the heat transfer mostly focuses on the heat transfer regularity and its transfer speed, not the exergy lost.…”
Section: Introductionmentioning
confidence: 99%
“…to search the optimal internal structure, external shape and time rhythm of one thing by taking performance maximization as an objective with given global constraints [2][3][4][5][6][7][8]17]. And the researches, which combine entransy dissipation extremum principle and finite time thermodynamics [55][56][57][58][59][60][61][62][63][64][65][66][67] with constructal theory [1-17, , are the new directions of this field.…”
Section: Introductionmentioning
confidence: 99%